2017
DOI: 10.1038/s41598-017-07036-8
|View full text |Cite
|
Sign up to set email alerts
|

Local opposite orientation preferences in V1: fMRI sensitivity to fine-grained pattern information

Abstract: The orientation of a visual grating can be decoded from human primary visual cortex (V1) using functional magnetic resonance imaging (fMRI) at conventional resolutions (2–3 mm voxel width, 3T scanner). It is unclear to what extent this information originates from different spatial scales of neuronal selectivity, ranging from orientation columns to global areal maps. According to the global-areal-map account, fMRI orientation decoding relies exclusively on fMRI voxels in V1 exhibiting a radial or vertical prefe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…In fact, decoding accuracy was unaffected (statistically indistinguishable) by shifting the slices. However, the finding that a coarse-scale bias is the source of orientation decoding remains controversial, and several recent studies have attempted to disprove it ( Alink et al, 2013 ; Pratte et al, 2016 ; Alink et al, 2017 ), in part, we believe, because the notion that fMRI is sensitive to fine-scale neural activity is highly attractive. We have no doubt that there are orientation columns in human V1.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In fact, decoding accuracy was unaffected (statistically indistinguishable) by shifting the slices. However, the finding that a coarse-scale bias is the source of orientation decoding remains controversial, and several recent studies have attempted to disprove it ( Alink et al, 2013 ; Pratte et al, 2016 ; Alink et al, 2017 ), in part, we believe, because the notion that fMRI is sensitive to fine-scale neural activity is highly attractive. We have no doubt that there are orientation columns in human V1.…”
Section: Discussionmentioning
confidence: 97%
“…However, in some cases, other stimulus vignetting exists, resulting in more subtle coarse-scale patterns of orientation bias ( Swisher et al, 2010 ; Larsson et al, 2017 ; Sengupta et al, 2017 ). One study ( Alink et al, 2017 ) used inner and outer circular annuli, but added additional angular edges, the result of which should be a combination of radial and tangential biases. Indeed, this study reported that voxels had a mixed pattern of selectivity, with a considerable number of voxels reliably preferring tangential gratings, and other voxels reliably favoring radial orientations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, the findings reported here provide intuitions into the sensitivity of multivoxel decoding to high and low spatial frequency information when the input stimuli contain both low and high spatial frequencies, which is not guaranteed to be the same as when low or high spatial frequency stimuli are presented in isolation. A recent study by Alink et al 36 implemented an analysis strategy comparable to the one adopted here to assess the spatial scale of information exploited by MVPA during orientation decoding in V1. They spatially offset the testing relative to the training set by 1, 2, 4, and 6 mm and measured the impact on decoding accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…We then tested the performance of 3 classifiers: linear SVM; Linear Discriminant Analysis (LDA); and Naïve Bayes Classifier (NBC) on real data. It should be noted that comparable, albeit slightly different approaches have previously been implemented to assess the scale of information exploited by MVPA during orientation decoding in V1 at 3 T. Alink et al 36 , for example, implemented an analysis strategy comparable to the one proposed here. They spatially offset the testing relative to the training set by 1, 2, 4, and 6 mm and measured the impact on decoding.…”
mentioning
confidence: 99%